2000
DOI: 10.1073/pnas.220427297
|View full text |Cite
|
Sign up to set email alerts
|

Endogenously expressed estrogen receptor and coactivator AIB1 interact in MCF-7 human breast cancer cells

Abstract: Coactivators are believed to mediate estrogen-induced gene responses via interaction with estrogen receptors (ER). Currently, a major challenge is to determine the importance of each coactivator in a specific cell type and promoter context in response to a particular ligand. The potential of ER to interact with a growing list of coactivators has been shown in a variety of in vitro and gene transfer assays, yet very few data have demonstrated the interaction of endogenous coactivators with ER in intact cells. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
35
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 25 publications
0
35
0
Order By: Relevance
“…Bautista et al (1998) also demonstrated that RAC 3 amplification correlated with both tumour size and ER and progesterone receptor (PR) positivity in primary breast cancers. It has further been shown that endogenous RAC 3 interacts with the human ER in a ligand-dependent manner in MCF-7 breast cancer cells (Tikkanen et al, 2000). Interestingly the RAC 3 gene has also been found to be amplified in pancreatic cancers and primary gastric cancers suggesting that RAC 3 is functional in non-primarily steroid-dependent organs (Ghadimi et al, 1999;Sakakura et al, 2000).…”
mentioning
confidence: 96%
“…Bautista et al (1998) also demonstrated that RAC 3 amplification correlated with both tumour size and ER and progesterone receptor (PR) positivity in primary breast cancers. It has further been shown that endogenous RAC 3 interacts with the human ER in a ligand-dependent manner in MCF-7 breast cancer cells (Tikkanen et al, 2000). Interestingly the RAC 3 gene has also been found to be amplified in pancreatic cancers and primary gastric cancers suggesting that RAC 3 is functional in non-primarily steroid-dependent organs (Ghadimi et al, 1999;Sakakura et al, 2000).…”
mentioning
confidence: 96%
“…Among the p160 coactivators, RAC3 AIB1 is clinically important because it is amplified in breast cancers (17). Furthermore, RAC3 forms a stable complex with estrogen receptor ␣ in breast cancer cells (27), suggesting that RAC3 may play an important role in the development of breast cancer.…”
mentioning
confidence: 99%
“…We have determined, using a regulatable AIB1-directed ribozyme, that downregulation of endogenous AIB1 levels results in loss of estrogen induction of MCF-7 breast cancer cell proliferation in vivo and in vitro (List et al, 2001a). AIB1 has been shown to directly interact with the ER in breast cancer cells (Tikkanen et al, 2000). Consistent with this, deletion of the AIB1 gene in mice leads to reduced development of the mammary gland (Xu et al, 2000).…”
Section: Introductionmentioning
confidence: 76%
“…Whole cell extracts were prepared as described previously (Harris et al, 2000), and equal portions (30 mg of protein) were resolved on denaturing 4-20% polyacrylamide gradient gels containing Tris-glycine. The separated proteins were transferred to a nitrocellulose membrane and then subjected to immunoblot analysis with a 1 : 500 dilution of a mouse monoclonal antibody specific for amino acids 376-389 of human AIB1 (Transduction Laboratories, Lexington, KY, USA), horseradish peroxidase-conjugated goat antibodies to mouse immunoglobulin (1 : 10 000 dilution; Amersham Pharmacia Biotech, Piscataway, NJ, USA), and enhanced chemiluminescence reagents (Amersham Pharmacia Biotech).…”
Section: Immunoblot Analysismentioning
confidence: 99%